PULSE WAVE VELOCITY AND ENDOTHELIAL FUNCTION COMPARISON IN HEALTHY PEOPLE AND CARDIOVASCULAR PATIENTS - Yu. I. Gurfinkel; N. V. Katse; L. M. Parfenova; I. Yu. Ivanova; V. A. Orlov (Российский кардиологический журнал)
The study aimed to identify the interrelations between pulse wave velocity (PWV) and endothelial function (EF), measured by a new non-invasive method vs. brachial artery Doppler ultrasound, as well as to investigate intima-media thickness (IMT) in carotid artery bifurcation area, in healthy people, patients with arterial hypertension (AH), and individuals with coronary heart disease (CHD). Comparing brachial-forearm PWV levels measured with the Tonocard device, and brachial artery linear blood flow velocity demonstrated statistically significant differences between velocity figures in healthy people, CHD patients, and AH participants. IMT values were significantly greater in CHD patients, but not in AH individuals, than in healthy people from the same age group. The new method for PWV and EF assessment provides an opportunity to evaluate CHD risk and risk-reducing therapy effectiveness in minimal time.